If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5x+2)=-6(-4x-3)
We simplify the equation to the form, which is simple to understand
2(5x+2)=-6(-4x-3)
Reorder the terms in parentheses
+(+10x+4)=-6*(-4x-3)
Remove unnecessary parentheses
+10x+4=-6+*(-4x-3+)
Reorder the terms in parentheses
+10x+4=+(+24x+18)
Remove unnecessary parentheses
+10x+4=+24x+18
We move all terms containing x to the left and all other terms to the right.
+10x-24x=+18-4
We simplify left and right side of the equation.
-14x=+14
We divide both sides of the equation by -14 to get x.
x=-1
| X^2-3x-73=0 | | 5(5x-3)=8+2x | | X^2-3x-3=70 | | 1/6x+1/8x+85=x | | 3x+5y+1=0 | | 2(2p-5)-3=-13+3p | | 4(1-6x)=-20 | | -6(3-3a)=18 | | -2(-6a-3)=-8 | | -6(v-6)+6=48 | | -2b-2b=-4 | | y/4=17/3 | | 2b-6b=16 | | k+3/8=5/9 | | -2r+8r=6 | | 1/2x=4x/1 | | y+c=20 | | b+5+4b=-5 | | 7-2x+x=-1 | | 2x^2+7m-4=0 | | 5(2x-1)+17=5x+6(x+2) | | 400=2500+2(a)(110) | | n+12=2 | | 6*(x-2)-8*(x-3)=16 | | 10=p/3 | | 6*(x-2)-8*(x-3)=-16 | | m/10=-3 | | 7x^2-22=34 | | -2x^3+8x-1=0 | | -3/7p=5/12 | | 3a-5=48-40a | | 32x^2+12x-2=0 |